Management of multiple myeloma in younger patients Therapie jüngerer Patienten mit multiplem Myelom - Strifler, S.; Einsele, H. (Onkologe, 2018)
Background: Considerable progress in overall survival has been made over the last 30 years in the treatment of multiple myeloma; however, the disease remains incurable in the majority of cases. Objective: Overview of approved and upcoming therapies for younger myeloma patients in the first-line and relapse situations. Material and methods: Synopsis of current treatment standards taking into account autologous and allogeneic stem cell transplantation and considering selected relevant studies. Discussion in the context of emerging new treatment options. Results: Bortezomib-based triplets followed by 1–2 transplantations of autologous stem cells and lenalidomide maintenance are the standard first-line treatment in younger patients. A second transplantation was demonstrated to improve progression-free survival in selected patients, e. g. in the presence of high-risk cytogenetics or inadequate response. Monoclonal antibodies and second generation proteasome inhibitors are used in relapse situations. Allogeneic transplantation can lead to long-term disease control in the first line as well as in relapse with appropriate patient selection (high-risk cytogenetics, successful reinduction). In addition to the use of immunologically active patient-specific cell therapies, targeted therapy can also be expected in the future within clinical trials. Conclusion: In biologically fit patients even above 65 years, a bortezomib-based triplet followed by 1–2 autologous stem cell transplantations and lenalidomide maintenance is the treatment of choice. The importance of tandem transplantation has not been conclusively clarified in standard risk patients against the background of new highly effective induction therapies but an improvement in survival has been demonstrated. Potentially curative allogeneic transplantation can be an option in these situations. In addition, immunological approaches are becoming increasingly important; however, it remains unclear to what extent these can compensate for the presence of risk factors and further improve survival.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic stem cell transplantation; Autologous stem cell transplantation; Bortezomib; Lenalidomide; Tandem transplantation